COMPUTATIONAL FLUID DYNAMICS STUDY OF TURBOJET TJ-24 COMBUSTION CHAMBER - Putra Hardaya, Adi
Turbojet TJ-24 is a micro gas turbine manufactured by Institut Teknologi Bandung to produce 24 N of thrust, and it has been the subject of numerous researches. However, the latest test showed that the turbojet cannot reach idle operation. Following the redesign of its diffuser in 2018, this research aims to study the current combustion chamber design using the methods of computational fluid dynamics (CFD). CFD simulations performed using ANSYS Fluent 16.0 gave results with acceptable convergence. Lowering the values of under-relaxation factors was an important step to obtain these results. However, boundary layers were not simulated accurately to attain convergent results. Simulations show that, without a gap between the front part of the flame tube and the inner casing, a stable and complete combustion was achieved in the combustion chamber. However, temperature distribution at combustor outlet was less uniform than what is usually acceptable in practice. It was also found that replacing a ninety-degree corner on the back of flame tube with a 3-mm chamfer eliminated recirculation near the inlet guide vanes and enabled a better velocity distribution at combustor outlet. Holes can be introduced to the combustor's inner casing to obtain a better temperature distribution. In the future, further research is needed to determine whether combustion outlet conditions obtained here are suitable for inlet guide vanes and turbine blades.